Penerapan Strategi Fokus Yareu Sebagai Upaya Meningkatkan Konsentrasi Belajar Anak Sekolah Dasar - Hanifah, Khansa Nur; Runy, Radina Raulia; Mutiarasani, Salsabil Illiyyin; Nurhafifah, Septiani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine how the YAREU focus strategy improves the learning concentration of elementary school children. The research method used was descriptive qualitative, with fourth-grade students at an elementary school in Bandung as subjects. Data were obtained through observation, teacher interviews, and documentation of learning activities. The results showed that the YAREU strategy, which focuses on breathing exercises, simple relaxation, and strengthening motivation, improved students’ concentration during learning. These findings demonstrate that the YAREU focus strategy can be used as an alternative, innovative learning method to support the achievement of more optimal learning outcomes.